Prosperity Gospel Latinos and Their American Dream - Lin, Tony Tian-Ren (Book collections on Project MUSE., 2020)
"Building on in-the-field immersive ethnographies and extended interviews conducted in Spanish in California, Virginia, and New York City (the NYC piece is new), Lin shows how Latino Pentecostals form a new "American" identity in the process of following the teachings of Prosperity Gospel Pentecostalism. While past studies have looked at how Latino immigrants become Pentecostals, Lin looks at how Latino Pentecostals become "American." This work arises from the intersection of two major trends transforming the United States in the twenty-first century. First, the rapid, continuing growth of the Latino population-many of them immigrants both documented and undocumented; second, the increasing influence of Prosperity Gospel Pentecostalism in American culture. (Just as Latinos have evolved from presenting as a relatively small and ignored population in the USA to one that wields significant economic and cultural influence, so has Prosperity Gospel Christianity, at one point mocked and derided in the mainstream, gained influence in American culture.)"--